Why do firms invest in the Baltic Sea Region - Markku Kotilainen; Nuutti Nikula (The Research Institute of the Finnish Economy (ETLA), 2010)
We have defined the Baltic Sea Region as consisting of the following countries and regions: Denmark, Estonia, Finland, Germany, Latvia, Lithuania, Poland, Sweden, and the regions of St Petersburg, Leningrad Oblast and Kaliningrad in Russia. We have investigated the factors af-fecting FDI in the Baltic Sea Region in three ways. First, we have studied the factors affecting FDI on the basis of the existing theoretical and empirical literature. Secondly, we have studied the characteristics of the existing FDI in the Baltic Sea Region. Thirdly, we have researched the investment motives through two firm questionnaires: 1) firms participating in the MIPIM real estate fairs and 2) Finnish firms active in the Baltic Sea Region (Finpro register). The common results of both empirical enquiries were: 1) the most important reasons for FDI are market size and its growth potential, 2) companies do not see the BSR as a single market in their actual decision making process, 3) there are clear benefits in having the non-Euro area countries as members of the EMU, but the results are not very robust: obviously they are weakened by the already rather credible pegs of the Estonian, Danish, Latvian and Lithuanian currencies and the diversification benefits of the floating Swedish krone, and 4) governmental investment promotion organizations have a rather small role in the actual investment decision making process. Their role is rather in giving general information on the country's investment environment. The most important differences between the samples of firms are: 1) in the real estate sector the majority of FDI is done through buying an existing firm, whereas in the sample of Finnish firms most FDI is done as a greenfield investment (establishing a new firm), 2) among the real estate firms Sweden, Finland, Germany and Poland are the most important destinations for FDI, while in the Finnish sample of firms (including more manufacturing and service firms) St Petersburg, Poland, Estonia and Sweden are the most important destinations, 3) in the sample of real estate firms R&D and the proximity of the Russian market are not important motives for FDI, contrary to the Finnish, more manufacturing and retail trade-oriented sample, and 4) among the real estate firms the potential for large increases in real estate prices is an important motive for FDI.
Keywords: F21; F23; F13; F15; 330; Foreign direct investment (FDI); Baltic Sea Region; Denmark; Estonia; Finland; Germany; Latvia; Lithuania; Poland; Sweden; St Petersburg; Leningrad Region; Kaliningrad